Analisis perbedaan pengaruh kebijakan suku bunga bank sentral terhadap inflasi di Indonesia - Kezia, Cristin; Amril, Amril; Vyn Amzar, Yohanes (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
The purposes of this study are (1) to analyze the effect of the BI rate on inflation (2) to analyze the effect of the BI 7 day reverse repo rate on inflation (3) to analyze the different effects of the BI rate and the BI 7 day reverse repo rate on inflation. The method used in this study uses secondary data sourced from Bank Indonesia and the Central Bureau of Statistics of the Indonesian financial economy. The analysis of this study with vector autoregressive (VAR) using the Eviews 10 software program, results of the study analyzed that the difference in the influence of the central bank's interest rate policy on inflation in Indonesia, that the BI rate of interest on inflation had a positive and significant effect with a benchmark of 5% or 0.005%, the analysis on the BI 7 day reverse repo rate is not significant at the benchmark of 5% or 0.005% but has a positive effect in reducing inflation in Indonesia which reflects price stability as the final target of monetary policy. Keywords: BI rate, BI 7 day reverse repo rate, Inflation, Vector autoregressive (VAR)